Implementation of Audio Visual Media to Improve the Quality of the Process and Learning Outcomes of Students at SD Negeri 4 Meurah Dua - Khairunnisa; Suryanti, Uli (Jurnal Pendidikan Profesi Guru, 2025)
Classroom Action Research was carried out at SD Negeri 4 Meurah Dua with a research subject that focused on grade V students totaling 22 students. This research is based on the lack of student learning outcomes in memorization. Based on the initial observations made previously, the learning process carried out before students directly memorized themselves individually, not guided by the teacher, so students were less courageous and confident in their memorization results. Another factor that is a problem in the memorization process is the lack of repetition. Therefore, audio visual is very suitable in whether through the implementation of Audio Visual media can improve the quality of the process and learning outcomes of grade V students of SD Negeri 4 Meurah Dua, Pidie Jaya Regency on the subject of telling the Story of the Prophet in the first semester of the 2024/2025 Academic Year. The implementation of learning outcomes also increased, namely in the first cycle 45.45% and in the second cycle it reached 86.36%. Based on these results, applying the tikrar method to the Telling the Story of the Prophet material has increased student learning outcomes. Likewise, the results of observations in the first cycle were 83% and the second cycle was 92.22%. Thus, the level of success of student activities based on the observations of the two observers is included in the category of very good.